Analysis Of Digital Economic Interactions, Economic Openness, Islamic Human Development Index (I-HDI) And Investment On Indonesia's GDP Growth - Imsar, Imsar; Nurhayati, Nurhayati; Harahap, Isnaini (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine the impact of the digital economy, economic openness, I-HDI and investment on Indonesia's GDP growth. Research data was collected in the form of a time series from the BPS and BI websites. The data is quarterly interpolated and analyzed using the VAR VECM method to find the impact of the digital economy, economic openness, I-HDI and investment in the short and long term periods. The findings show There is a causal relationship between IHDI and the digital economy, digital economy and GDP, GDP and IHDI, IHDI and GDP, GDP and investment, economic openness and GDP. 2) There is a positive and significant relationship between the digital economy, economic openness, IHDI and investment on the growth of Indonesia's Gross Domestic Product in the long term, while in the short term all variables have no significant effect on Indonesia's GDP growth. In the long term, a strong and dominant variable influencing GDP growth is investment. 3) The largest composition that contributes to the Gross Domestic Product (GDP) variable is the digital economy (32%) and IHDI (27.4%).